The use of Time-Based Activity Based Costing (TDABC) and its role in increasing competitive advantage in Saudi business organizations - Ibrahim, El Hadi Adam Mohamed; Khaled, Hassan Awad Hassan; Mudawa,AbdulBaqi MudawaAl-Asha (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed at revealing the importance of applying modern cost systems and clarifying their role in increasing the competitive advantage of many industrial establishments, and their role in increasing competitive advantage. What is the role of applying the Activity based cost system in support of competitive advantage? The aim of the study was to identify the role of the Activity based cost system in increasing product quality. The study concluded that there is a statistically significant relation between the Activities based cost system and increasing the competitive advantage in the Saudi manufacturing enterprise. The study concluded with several recommendations, including the industrial establishments Saudi Arabia is interested to apply the Activity based cost system because of its active role in increasing the competitive advantage.